2022
DOI: 10.1186/s42522-022-00065-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental cross-species infection of donkeys with equine hepacivirus and analysis of host immune signatures

Abstract: Background The Equine Hepacivirus (EqHV) is an equine-specific and liver-tropic virus belonging to the diverse genus of Hepaciviruses. It was recently found in a large donkey (Equus asinus) cohort with a similar seroprevalence (30%), but lower rate of RNA-positive animals (0.3%) compared to horses. These rare infection events indicate either a lack of adaptation to the new host or a predominantly acute course of infection. Methods In order to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…On the other hand, adaptive immune responses were shown to have a strong effect on virus replication. In this and previous studies, virus copy numbers decrease with the appearance of anti-EqHV antibodies ( 18 20 , 26 , 32 ). Similarly, HCV in chimpanzees and humans is often eliminated with co-occurrence of strong adaptive immune responses ( 38 , 55 , 56 ).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…On the other hand, adaptive immune responses were shown to have a strong effect on virus replication. In this and previous studies, virus copy numbers decrease with the appearance of anti-EqHV antibodies ( 18 20 , 26 , 32 ). Similarly, HCV in chimpanzees and humans is often eliminated with co-occurrence of strong adaptive immune responses ( 38 , 55 , 56 ).…”
Section: Discussionsupporting
confidence: 80%
“…In previous EqHV infection studies, most animals were acutely infected and prolonged viremia was rarely observed. Inoculation techniques have varied, with inoculation volumes ranging from 1 to 500 mL serum or plasma, corresponding to approximately 2 × 10 4 to 3.9 × 10 9 RNA copies per infection ( 19 , 20 , 26 , 32 ). In addition, inoculation with serum or plasma often has the disadvantage that the host immune system, especially at high doses, could trigger an early and strong immune response that contributes to viral clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations